Surface functionalization of magnetite nanoparticle: A new approach using condensation of alkoxysilanes - Rodriguez, A. F. R.; Costa, T. P. [UNESP]; Bini, R. A. [UNESP]; Faria, F. S. E. D. V.; Azevedo, R. B.; Jafelicci, M. [UNESP]; Coaquira, J. A. H.; Martinez, M. A. R.; Mantilla, J. C.; Marques, R. F. C. [UNESP]; Morais, P. C. (Elsevier B.V., 2017)
In this study we report on successful production of two samples (BR15 and BR16) comprising magnetite (Fe3O4) nanoparticles (similar to 10 nm) surface-functionalized via hydrolysis and condensation of alkoxysilane agents, namely 3-aminopropyl-trimethoxisilane (APTS) and N-propyl-trimethoxisilane (NPTS). The as-produced samples were characterized using transmission electron microscopy (TEM), x-ray diffraction (XRD), magnetization measurements (5 K and 300 K hysteresis cycles and zero field-cooled/field-cooled measurements), and Mossbauer spectroscopy (77 and 297 K). The Mossbauer data supported the model picture of a core-shell magnetite-based system. This material system shows shell properties influenced by the surface-coating design, either APTS-coated (BR15) or APTS+NPTS-coated (sample BR16). Analyses of the Mossbauer spectra indicates that the APTS-coated sample presents Fe(III)-rich core and Fe(II)-rich shell with strong hyperfine field; whereas, the APTS+NPTS-coated sample leads to a mixture of two main nanostructures, one essentially surface-terminated with APTS whereas the other surface-terminated with NPTS, both presenting weak hyperfine fields compared with the single surface-coated sample. Magnetization measurements support the core-shell picture built from the analyses of the Mossbauer data. Our findings emphasize the capability of the Mossbauer spectroscopy in assessing subtle differences in surface-functionalized iron-based core-shell nanostructures.
Keywords: Magnetite nanoparticles; Surface-functionalization; Hydrolysis and condensation reactions; X-ray diffraction; Mossbauer spectroscopy; Zero-field-cooled/field-cooled traces